Blind Turbo equalization algorithm based on hidden Markov model for continuous phase modulation signals - Kai ZHONG; Hua PENG; Lin-dong GE (Tongxin xuebao)
To solve the issues of the poor performance and convergence difficulties in the blind equalization of high order continuous phase modulation (CPM) signals, a new EM-SOVA channel blind equalization method was developed from the perspective of hidden Markov model(HMM). A novel blind Turbo equalization algorithm for high order CPM signals was proposed based on the combination of this method and Turbo equalization. The algorithm improved the equalization performance by applying the soft-output Viterbi algorithm(SOVA) within an EM iteration. Simultaneously, a soft infor-mation iterative process was used for further improvement of the system performance at a low signal-to-noise ratio. The analysis and simulation results show that the proposed algorithm provides a good blind equalization performance and convergence.